Perceived impact of online written feedback on students' writing and learning: a reflection. Issue 6 (2nd November 2017) - Delante, Nimrod L.
Abstract: In this reflective study, I perceive the impact of my own written feedback on students' academic writing skills in particular and on learning in general. Anchored on Schon's reflection-on-action (ROA) framework, my reflection arose from a content analysis of my written feedback on 80 student drafts and 44 feedback responses. I found that my written feedback is of two types: focus on form and focus on meaning . Coding the feedback led to an identification of six feedback functions: instructive/using imperatives (18.36%); suggestive (15.31%); asking questions/probing (23.98%); stating a personal opinion (6.12%); corrective (29.59%); and affirming/negating (6.63%). The categorisation of feedback according to these functions was influenced by Wolsey's feedback functions (2008) which was adapted by Alvarez, Espasa and Guasch. Results revealed that I employ corrective feedback, probing questions and instructive feedback more frequently than suggestive feedback, personal statement or affirmation/negation. I also found that my feedback on form (59%) is higher than my feedback on meaning (41%). I explain the relationship of these findings by identifying some confounding factors that enabled me to interrogate my assumptions, along with a discussion of their implications.